Another way of being a woman: the struggle of Zapatist women from a decolonial analysis (1999-2007): Outra forma de ser mulher: a luta das mulheres Zapatistas a partir de uma análise decolonial (1999-2007) (Revista de História da UEG (REVHIST), 2021)
This article aims to analyze based on the struggle for female emancipation in Zapatista territory, which the demands of women working in the movement and its ideals of struggle applied in accordance with their contexts and local realities, located in Latin America and more specifically in Mexico, in which they vehemently seek to maintain their cultural roots with minimal interference from universalist or Eurocentric ideals. In this sense and through the analysis of letters and public speeches registered in historical archives. Firstly, we will focus on the historical context of the Zapatista Army, which is constituted as a revolution of a decolonial character, and then of “being a woman” in the face of the reality of the Zapatistas and what are their ways of fighting in this context of decolonial feminist struggle inherent in the issues that pass through the conceptions designed by other hegemonic feminisms. With this and through the statements of the Zapatistas left in writing we will answer what are the problems that move the struggle of these subjects within a revolutionary and decolonial context.Keyword: Zapatista women. Decolonial feminism. Decoloniality. Zapatistas.